Crassifolins Q−W: Clerodane Diterpenoids From Croton crassifolius With Anti-Inflammatory and Anti-Angiogenesis Activities - Li, Canjie; Sun, Xin; Yin, Wenjing; Zhan, Zhaochun; Tang, Qing; Wang, Wenzhi; Zhuo, Xuefang; Wu, Zhongnan; Zhang, Haipeng; Li, Yaolan; Zhang, Yubo; Wang, Guocai (Frontiers in Chemistry, 2021)
Seven new clerodane diterpenoids, crassifolins Q−W (1–7), along with five known analogues (8–12), were isolated from the roots of Croton crassifolius. Their structures were identified by comprehensive spectroscopic analysis (UV, IR, NMR, and HR-ESI-MS), and their absolute configurations were determined by ECD spectra and X-ray crystallography. The activities of compounds 1–5 against inflammatory cytokines IL-6 and TNF-α levels on LPS-induced RAW 264.7 macrophages were assessed, and compound 5 showed the most significant activity with the secretion levels of IL-6 and TNF-α at 32.78 and 12.53%, respectively. Moreover, compounds 1–5 were screened for their anti-angiogenesis using a human umbilical vein endothelial cells in vitro mode; the results showed all of them exhibited obvious anti-angiogenesis activities, in particular, compound 5 showed the strongest anti-angiogenesis effect in the range of 6.25–50 μM.